The mesosomal gland of Xylocopa frontalis (Hymenoptera, Apidae, Xylocopini) - Costa, Moyses [UNESP]; Nocelli, Roberta Cornélio Ferreira [UNESP]; Netto, José Chaud [UNESP] (My University, 2006)
Males of Xylocopa fimbriata and X. micans present mesosomal glands that produce secretions containing many volatile substances with an intense floral fragrance, which resembles the fragrance produced by flowers that are attractive to the females of both species. The mating territories occupied by males of X. frontalis have no helpful resources for the females of this species, which are probably attracted to these environments by sexual pheromone(s) produced in the male mesosomal glands (lek polygyny). In this work, the presence of these glands in males of X. frontalis was confirmed and their anatomy and ultrastructure were described. An attempt to correlate the morphological characteristics of the mesosomal glands with the male territorial behavior was also carried out.
Keywords: Lek polygyny; Mating behavior; Mesosomal glands; Territoriality; Xylocopa frontalis; Apidae; Hymenoptera; Xylocopa micans; Xylocopini